The effects of developmental stimulation intervention on the growth, development and degree of maternal attachment of pre-term infants - Dial, Myrna Novilunio
This research study focused on 1 specific question: Would early intervention through environmental stimulation of the pre-term infant influence his growth, development and degree of maternal attachment? To answer the question, 3 hypotheses were formulated. 1. At 8 weeks of age, pre-term infants who are subjected to environmental stimulation will have significantly greater weights and lengths than pre-term infants not subjected to environmental stimulation. 2. Pre-term infants who are subjected to environmental stimulation will have significantly less delays on the MMDST than pre-term infants not subjected to environmental stimulation. 3. Mothers of pre-term infants who are subjected to environmental stimulation will have significantly higher scores in maternal attachment than mothers of pre-term infants not subjected to environmental stimulation. This field study followed an experimental model and utilized a 2-group, before and after design. The independent variable was the developmental stimulation intervention using a multimodal approach. The dependent variables were growth (i.e., weight, length), behavioral development (MMDST performance), and maternal behavior. Data analysis on weight, length, maternal attachment and behavioral development was done by means of the T-test. 4 hypotheses were formulated to test the effects of environmental stimulation program in terms of 4 variables namely: 1) weight, 2) length, 3) maternal attachment, and 4) MMDST delays. Based on the findings of this study and on the clinical observations made during the experimental period, the developmental program set forth in this study deserves a trial in nurseries of other hospitals. With reference to the methodology, the 4-group design as suggested by Gottfried and Cornell (1974) permits a more thorough analysis and provides more information than either the pre-test post-test or the post-test only control group design. A similar study is recommended to corroborate or supplement the findings of this study, as well as provide controls of extraneous variable. The said program maybe incorporated into the parenthood education program designed for parents, which if implemented would not only foster confidence in the care-taking ability of the mothers but would also improve parent-infant interaction thus fostering child growth and development and improve feeling of personal growth.